Primary frequency modulation of microgrid based on consistent droop control method. Issue 1 (1st November 2022) - Hu, Linlin; Fu, Long
Abstract: The rapid development of new energy sources gradually challenges the frequency stability of power systems. This article focuses on how to realize the frequency modulation control of the power grid under the fluctuation of the power grid. In order to improve the frequency stability of the microgrid system, based on the traditional droop control and consensus algorithm research, this paper proposes a microgrid primary frequency modulation based on the consistency droop control method. This control strategy improves the consistency of the progressive correction term to realize the control of the output of the energy storage unit, and improves the traditional droop controller to quickly restore the stability of the primary frequency. The root locus method verifies the effectiveness and feasibility of the control strategy. The simulation experiment verifies the frequency modulation ability of the proposed control strategy, which not only has a faster adjustment speed and response ability, but also has a strong anti-interference ability.